Postharvest technology of perishable horticultural commodities - Yahia, Elhadi M. (Elsevier, WP, 2019)
"Presents the most recent developments in processing technologies in a single volume Includes a wide range of perishable products, thus allowing for translational insight Appropriate for students and professionals Written by experts as a reference resource"- Resumé vydavatel